Gentrification without Gentry in a Declining Global City?: Vertical Expansion of Tokyo and Its Urban Meaning. Issue 1 (25th March 2021) - Machimura, Takashi
Abstract : This article explores the reasons for the vertical expansion of cities till the 2020s by analyzing the history of urban space production for about half a century, using Tokyo as an example. As a concept, gentrification partially explains the changes in Tokyo. However, summarizing the entire urban transformation as a gentrification trend can lead to some misunderstandings. Most of the development took the form of simply rebuilding skyscrapers in limited areas, rather than the displacement of an entire class in the whole district. Consequently, the sharp contrast between island‐like skyscrapers and the densely populated small houses surrounding them became the typical landscape of current semi‐gentrified Tokyo. Instead of gentrification, "gentrification without gentry" would be a better expression for describing most cases in Tokyo. Alliances for urban speculation are always embedded in multi‐scale conditions in a globalizing world along with the inherent historical and structural constitution of the city. Through dynamic but contingent processes, a structure was constructed to promote urban development in a way that might exceed the actual demands. In the case of Tokyo, the bubble economy era and its effects, a would‐be global city ideology, mega‐events such as the Olympic Games, and expected earthquakes had a distinct influence on other common factors.